Strategic analysis for sustaining production and saving water through increasing t. Aus and t. Aman rice cultivation in Bangladesh: Strategic analysis for sustaining production and saving water - Salam, M A; Iftekharuddaula, K M; Salam, M U; Hasan , M M (Bangladesh Journal of Agriculture, 2026)
Rice is a water-loving crop. Among the three rice growing seasons of Bangladesh, water demand is met in Boro through intensive irrigation largely utilizing underground water. Increasing pressure on underground water can cause water crisis in future hindering irrigation coverage of the entire production area in the season. With this background, this study explored revised seasonal land allocation between the rice growing seasons aiming probable land release from Boro season to sooth water crises. Options were also included in utilizing fallow land in their process. A conceptual framework was developed to address the issue. For the analysis, published and unpublished data were used. A model was developed and applied to simulate rice area, yield and production under four different scenarios. The results shows that the area under T. Aus can be increased from 1.28 to 2.0 mha in 2030 by utilizing 15% fallow land and shifting 5% of Boro area to T. Aus. Utilization of better varieties and proper management practices would ensure the target of rice production equilibrium in the proposed change scenarios, whereas mitigate potential water crisis by 4725 million liters. To establish these potentials, the study highlighted a number of pre-requisites to be looked into by various stakeholders. Bangladesh J. Agri. 2025, 50(2): 38-55